2019
DOI: 10.1007/s13555-019-00330-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of Topical Nitric–Zinc Complex Solution to Treat Palmoplantar and Periungual Warts in a Pediatric Population

Abstract: Introduction: Nitric-zinc complex solution (NZCS) is a topically applied solution containing nitric acid, zinc, copper, and organic acids that induce a painless caustic effect on ''difficult-to-treat'' warts, including palmoplantar and periungual locations. The objective of the present prospective clinical study was to describe the efficacy and tolerability of NZCS in the treatment of palmoplantar and periungual warts in children. Methods: Eligible patients were immunocompetent children and adolescents, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…There is limited data on the efficacy and safety of other topical therapies for the treatment of warts in children. Reported clearance rates were 99% for formalin with or without curettage, 83.9% for nitric‐zinc complex solution, 81.8% for pyruvic acid, 78.3% for promicid gel under occlusion, 73.3% for promicid gel without occlusion, 59.3% for monochloroacetic acid (MCA), 56.3% for silver nitrate, 42.9% to 100% for retinoids (including adapalene) and 22.2% for cantharidin 12‐14,17,24,26,33,36‐39 Side effects reported in some of the studies included pain (75.8%) and blistering (36.7%) with MCA 24 and pain, stinging or soreness with promicid gel (33.9%) 39 . No side effects were reported in studies for nitric‐zinc complex solution or adapalene gel 26,37 …”
Section: Resultsmentioning
confidence: 99%
“…There is limited data on the efficacy and safety of other topical therapies for the treatment of warts in children. Reported clearance rates were 99% for formalin with or without curettage, 83.9% for nitric‐zinc complex solution, 81.8% for pyruvic acid, 78.3% for promicid gel under occlusion, 73.3% for promicid gel without occlusion, 59.3% for monochloroacetic acid (MCA), 56.3% for silver nitrate, 42.9% to 100% for retinoids (including adapalene) and 22.2% for cantharidin 12‐14,17,24,26,33,36‐39 Side effects reported in some of the studies included pain (75.8%) and blistering (36.7%) with MCA 24 and pain, stinging or soreness with promicid gel (33.9%) 39 . No side effects were reported in studies for nitric‐zinc complex solution or adapalene gel 26,37 …”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, only one randomized clinical trial has been published to date on treating AGW with the nitric–zinc complex, 12 making the present study the first clinical trial to evaluate its efficacy in plantar warts. Notably, case series examining the treatment of palmoplantar warts with the zinc–nitric complex have reported very high cure rates, with Cusini et al 14 observing a 100% cure rate and Giacaman et al 15 reporting a cure rate of 71%. Furthermore, Giacaman et al observed an 87.5% cure rate for periungual warts 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 12 pediatric subjects used nitric zinc complex solution to treat periungual warts, palmar warts, and plantar warts and found 83.9% clearance. Some patients experienced mild burning sensation and pain [29]. This presents as an easily accessible and safe option for the pediatric population.…”
Section: Pulsed Dye Lasersmentioning
confidence: 98%